Rozpad ZSRR i jego konsekwencje w postaci rekonstrukcji oraz modyfikacji więzi łączących Rosję z państwami obszaru poradzieckiego - Jastrzębska, Olga (Europa Orientalis. Studia z Dziejów Europy Wschodniej i Państw Bałtyckich, 2020)
The collapse of the USSR and its consequences in the form of reconstruction and modification of ties connecting Russia with the countries of the post-Soviet area The main topic of this article are the consequences of the process of the USSR collapse, expressed in the form of the bonds currently existing in the post – Soviet area, reconstructed by modern Russia, which is renewing or giving a new char-acter and strenghtening it’s position in the post – Soviet space and consequently in the international area. These bonds exist not only in the political and economic sphere, but also in social and cultural fields and have an influence on the assump-tions of Russian policy being formed today. The presented article we try to present these connections resulting from the break – up of the former USSR, their forma-tion on the basis of the aparted state, and the significance of their possible devel-opment in the future for those wishing to return to the power position of Russia in the international area.